EARNED VALUE ANALYSIS METHOD FOR EVALUATION TIME AND COST IN THE PROJECT X - Fransiscus Xaverius Juan Even; Fauziah Shanti Cahyani Siti Maisarah; Fauzi Akbar Rahmawan (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
The implementation of building construction projects, especially Project X, is quite complex and costly in terms of time and expenses. Of course, in project implementation, the factors of planning and controlling time and costs are crucial to the project's success. Therefore, this study aims to evaluate time and expenses using the EVA method. In this context, EVA is used as a method considered sufficiently effective and efficient in analyzing time and cost evaluations for project completion. The findings of this study indicate that the project contract value is IDR 638,553,623,000, with an SPI value of 0.738 in week 84, while the CPI value in week 84 is 0.932. In terms of time, there is a deviation from the established standard of 2 years and 6 months of implementation. From these two aspects, it can be concluded that the time and cost set at the beginning of the project refer to delays in implementation and cost overruns in this project, so the existing implementation methods must be changed, especially project performance and cost payments, which must be carried out on time and in accordance with the plan.